Effect of Carrier Agents on the Physicochemical and Technofunctional Properties and Antioxidant Capacity of Freeze-Dried Pomegranate Juice (Punica granatum) Powder - Adegoke Olusesan Adetoro; Umezuruike Linus Opara; Olaniyi Amos Fawole (Foods, 2020)
The physicochemical and technofunctional properties and antioxidant capacity of freeze-dried “Wonderful” pomegranate juice powder (PJP), produced with different carrier agents, were investigated. Powders were produced using maltodextrin, gum Arabic, and waxy starch as carrier agents and characterised by scanning electron microscopy (SEM) and particle size distribution. Results showed that PJP produced with maltodextrin had the highest yield (46.6%), followed by gum arabic (40.6%), while waxy starch had the least yield (35.4%). Powders produced with maltodextrin (96.5%) and gum arabic (96.1%) were highly soluble, which indicates better reconstitution properties. Waxy starch-added PJP had the lowest hygroscopicity (4.7%), which offers good stability during storage and a lower degree of caking compared to maltodextrin (10.2%) and gum arabic (12.6%) powders. Powders obtained from maltodextrin and gum arabic exhibited larger particle diameters ranging between 12 to 120 µm while the lowest particle diameter range was with powders formed from waxy starch (8–40 µm). Freeze-dried pomegranate powder produced with maltodextrin retained more redness (a*) by approximately 44%, compared to gum arabic. Similarly, PJP with maltodextrin and gum arabic had higher total soluble solids (10.3 and 10.4 °Brix), respectively. Total anthocyanin content was 54% more in PJP with maltodextrin than waxy starch PJP. Similarly, the powder produced with maltodextrin had higher radical scavenging activity (33.19 mM TE/g dry matter; DM) compared to gum arabic (28.45 mM TE/g DM) and waxy starch (26.96 mM TE/g DM). Overall, maltodextrin reflected the most suitable carrier agent to produce PJP.